Effect of climate change on agricultural output in Ethiopia - Adamu Mulu Ketema; Kasahun Dubale Negeso (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2020)
Currently change in climate is known as the main environmental difficult that the world face. Its effect is openly reduces agricultural output in particular and economic growth in general. The main objective of the study was to examine the long run and short run effect of climate change on agricultural output in Ethiopia over a period of 1980-2016. The Auto Regresive Distributive Lag approach to co integration was applied to examine the long run and short run effect of climate change on agricultural output. ADF test was used for Unit root test. Result of bound test reveals that there is stable long run relationship between RAGDP, labour force, Mean annual rainfall, Average temperature, agriculture land, and fertilizer input import. The estimated long run model reveals that climate changes have an important effect on agricultural output which is the main contributor of overall GDP of the country. The coefficient of error correction term is -0.738 suggesting about 73.8% annual adjustment towards long run equilibrium. The estimate coefficients of short run show that mean annual rainfall have significant effect whereas average temperature has insignificant effect on output. In the long run both main variable of interest have significant effect on agricultural output with a positive effect from mean annual rainfall and negative effect from average temperature. In order to lessen the effects the study recommends concerned body needs to create a specific policies especially focus on technological adoption that avert effect of increase in temperature and that would result increase on the output by adopting technology at macro and micro level, additionally information regarding climate should be available for producers and consumer.